Health in south-eastern Europe: a troubled past, an uncertain future - Bernd Rechel; Nina Schwalbe; Martin McKee (The World Health Organization, 2004)
The political and economic turmoil that occurred in south-eastern Europe in the last decade of the twentieth century left a legacy of physical damage. This aspect of the conflict has received considerable coverage in the media. However, surprisingly less has been reported about the effects of that turmoil on the health of the people living in the region. In an attempt to identify and synthesize data on these effects, we carried out a systematic review and used the results to put together a searchable online database of documents, reports, and published material, the majority of which have not previously been easily accessible (http://www.lshtm.ac.uk/ecohost/see/index.php). The database covers the period from the early 1990s to 2003 and will be of considerable interest to policy-makers. It contains 762 items, many of them annotated and available for downloading. This paper synthesizes the main findings obtained from the material in the database and emphasizes the need for concerted action to improve the health of people in south-eastern Europe. Furthermore, we also recommend that agencies working in post-conflict situations should invest in developing and maintaining online databases that would be useful to others working in the area.